Secondary Biology Education Research in Southeast Asia (2020 – 2025): A Bibliometric Analysis and Its Implications in Teaching Biology - Medida, Joahna (International Journal of Arts, Sciences and Education, 2026)
Research in secondary biology education plays a major role in the development of teaching pedagogies, curriculum alignment, and student learning outcomes. Academic interest in biology education across Southeast Asia has drastically increased recently, with regard to curriculum enhancements, student-centered instructions, and technology-enhanced instruction. However, a systematic mapping of research productivity, thematic directions, and collaboration patterns in Southeast Asia remains limited. Examining these trends may provide valuable insights into regional research themes that are dominant and their implications for biology teaching. This study mapped and analyzed research in secondary biology education in Southeast Asia from 2020 to 2025 using bibliometric analysis. A total of 99 Scopus-indexed publications were analyzed to examine publication trends, leading journals, authors, institutions, and countries, as well as collaboration networks and thematic evolution in the region. Bibliometric indicators and visualization tools, including Biblioshiny and VOSviewer, were utilized to examine research productivity, co-authorship patterns, keyword co-occurrence, and emerging research themes in secondary biology education in Southeast Asia from 2020 to 2025. The findings revealed a noticeable increase in publication output toward the latter years of the period, indicating growing research interest in secondary biology education in the region. Indonesia and the Philippines emerged as the most productive contributors, supported largely by national and university-based journals. Thematic analysis showed that in Southeast Asia, student-centered pedagogical approaches, STEM education, assessment practices, and technology-enhanced biology teaching such as blended learning and digital tools dominate the research landscape. Emerging themes emphasized an increasing focus on inquiry-based learning, critical thinking, and digital pedagogies, while collaboration networks suggest that international research partnerships were limited but gradually expanding. The results reflected Southeast Asia’s emphasis on context-responsive and practice-oriented research aligned with ongoing educational reforms. The study concluded by discussing implications for biology teaching, emphasizing the need for evidence-informed instructional practices and stronger research collaboration to further advance secondary biology education in the region.